Effect of Marketing Strategy Factors on Marketing Performance of Food Home Industry in Malang City - Triwijayati, Anna; Oentoro, Adhipramana; Winata, Christian Yudha; Prasetya, Raka Novian Adi (Sinergi International Journal of Management and Business, 2024)
This research examines factors or types of marketing strategies and marketing performance. The aim of the research is to examine the factors of each variable and the influence of marketing strategy factors on the performance of marketing strategies in the home food industry in Malang City. The research is in the form of a survey with a type of causal research. The number of samples was 398, taken from the food and beverage processing industry in Malang City. Data was collected through a survey using a questionnaire. Data were analyzed using the Structural Equation Modelling (SEM) Partial Least Squares (PLS) method. The research results explain that the marketing strategy factors formed are cost efficiency, product innovation, marketing innovation, and distribution channels. Meanwhile, the effectiveness of marketing strategy performance can be measured by increasing sales, market share and customer satisfaction. In further testing, cost efficiency, innovation and effective distribution factors influence marketing performance. This research provides benefits for the food home industry that product innovation, marketing, distribution and cost leadership strategies are very important to increase consumer satisfaction. Increased consumer satisfaction will have an impact on increasing market share, product sales, and profit sustainability.